ISOLASI PEKTIN DARI KULIT BUAH KAKAO (Theobroma cacao L.) DAN UJI DAYA SERAPNYA TERHADAP LOGAM TEMBAGA (Cu) DAN LOGAM SENG (Zn) - -, MAULIDIYAH; -, HALIMATUSSADIYAH; SUSANTI, FITRI; NURDIN, MUHAMMAD; -, ANSHARULLAH (Jurnal Agroteknos, 2014)
Isolation of pectin was carried out from rind cocoa (Theobroma cacao L.) and its adsorption capacity to Cu and Zn metals. Isolation method was performed using several steps such as preparation of raw materials, extraction, coagulation, sedimentation, washing, drying, and refinement of pectin. This isolation was performed at pH 2.8 with extraction time of 120 minutes at 95oC. The pectin obtained was analyzed its yield, moisture, ash, metoxile, and galacturonate contents, then continued by FT-IR spectrophotometer and analysis of trick adsorption of Cu and Zn which measured by Atomic Absorption Spectrophotometer. The result showed that the pectin  obtained were 5,03 % of metoxile and 47,96 % of galacturonate contents with 0,84 % of yield,  3,55 % of moisture, and 3,60 % of ash contents. IR spectrum showed that pectin has hidroxyl and carboxyl functional groups. Adsorption capacity of pectin on Cu and Zn were 90.71 % and 87.55 %, respectively. Keywords: Adsorption Capacity, Cu and Zn Metals, Pectin, Rind Cacao.